Laboratory and numerical analysis on the effect of using coconut fibre as additive towards residual shear strength of soil for slope construction / Juhaizad Ahmad ... [et al.] - Ahmad, Juhaizad; Rughan, Nurfarihah Raihan; Ibrahim, Anas; Rosli, Mohd Ikmal Fazlan; Abdul Rahman, Abdul Samad (Universiti Teknologi MARA Cawangan Pulau Pinang, 2023)
Rapid development of Malaysia has caused population growth in urban areas. This includes new development near slope areas. Utilization of waste material such as coconut fiber could help to increase the slope stability. There is a limited study on the effects of coconut fibre as an additive for slope construction. This study aims to compare the shear strength between treated and untreated residual soil and to assess the Factor of Safety (FOS) with coconut fibre addition using Slope/W. A total of 15 shear box samples were set at the same percentage of coconut fibre (1% by weight of soil). Coconut fibre with different length of 15mm, 25mm, 35mm and 45mm was used in the study. It was found that coconut fibre could increase the shear strength. The optimum length of coconut fibre to achieve the maximum friction angle is 35mm, with soil internal friction angle of 52.15ᵒ. Moreover, the Slope/w analysis is conducted to analyse the slope's safety factor. The slope's safety factor increased significantly with the addition of coconut fibre. Based on the findings, this research could shed some light on the effect of coconut fibre incorporated in soil as an additive to improve the shear strength. Using coconut fibre in slope stabilisation could reduce slope failure and at the same time could save the environment by utilizing this waste material.